Многоступенчатый осевой утилизационный турбодетандер для работы с потребителями газа разных давлений - Шубенко, Александр Леонидович; Сарапин, Владимир Павлович; Сенецкий, Александр Владимирович; Пащенко, Наталья Викторовна (НТУ "ХПИ", 2016)
Рассмотрен вариант реализации утилизационной турбодетандерной установки (УТДУ) на газораспределительной станции (ГРС) с потребителями природного газа различного давления. Проанализированы несколько ГРС и газораспределительных пунктов (ГРП) для определения параметров природного газа. Проведены расчетные исследования для выбора УТДУ с отборами и предложена 10-ступенчатая конструкция турбодетандера осевого типа мощностью 2600 кВт. Выполнены расчеты проточной части турбодетандера (ТД) в одномерной постановке и проведено исследование эффективности работы проточной части турбодетандера на переменных режимах эксплуатации с использованием современного программного комплекса для трехмерных газодинамических расчетов IPMFlow. Показано, что адиабатический КПД проточной части турбодетандера в среднем по режимам составляет 81 % при изменении мощности от 35 % до 100 %.

The variant of implementation of the energy recovery turboexpander unit at gas distribution stations to consumers of natural gas with different pressure is considered. Several distribution stations with various parameters of natural gas (flow, pressure) are reviewed. The calculations for design of the energy recovery turboexpanders with intermediate gas extraction from the flow pathare made. Axial type of turboexpander is proposed with the flow part which consists of ten stages. Each stage contains a nozzle and impeller. The design of the turboexpander is proposed to use two gas extraction from the flow path. Camera data are required to maximize the potential energy of the gas flow. The capacity of this unit will be 2600 kW. The calculations of the flow of the turboexpander in the one-dimensional calculation are made. The result of this calculation, the obtained geometric characteristics of the profiles of nozzle and rotor blades are shown. Further studies have been conducted of the effectiveness of the work flow of the turboexpander at variable operating conditions. Studies carried out with the usage of modern software for three-dimensional gas dynamic calculations IPMFlow. The calculations showed that the adiabatic efficiency of the flow part of the turboexpander is 81 % with the power changing from 35 % to 100 %.
Multistage turboexpander of axial type for energy recovery for working with natural gas consumers, who demand different pressure
Keywords: газораспределительная станция; газораспределительный пункт; проточная часть; ступень турбины; отсек; газодинамический расчет; переменный режим; gas distribution station; flow path; stage; variablemode